Cover crop technology – a way towards conservation agriculture: A review - SINGHAL, VIBHA; GHOSH, JYOTIRMOY; JINGER, DINESH (The Indian Journal of Agricultural Sciences, 2021)
There is transformation of agriculture from traditional to contemporary to fulfill the growing demand of food grains by mushrooming human population in the past few decades. Contemporary agriculture is completely dependent on external inputs of synthetic fertilizers and pesticides. Though it increased agricultural yield by many folds, but contributed to environmental degradation significantly including greenhouse forcing. The relevance of conservation agriculture emerged in response to the questions raised on health, environment and sustainability issues. Interest in conservation agriculture revived the traditional practices of cover cropping for soil conservation in the recent past. It is a form of reduced tillage improving soil physico-chemical and biological properties, claiming protection against insect-pests besides suppressing weeds effectively. In the present scenario, the role of cover crops extended to soil carbon sequestration thus combating global warming. Mean annual carbon sequestration potential of cover crop was found to be 0.32 ± 0.08 Mg ha−1 yr−1 to an average maximum increase of 16.7 Mg ha−1. Cover crops control weeds through competition, allelopathy, and/or physical effects due to surface residue, thereby interfering with growth, development and reproduction of weed. Cover crops suppress diseases by extending the length of a crop rotation, improving soil structure, providing a physical barrier and enhancing suppressive effects of soil life therefore disrupting disease cycle phases. Species in the brassicaceae family, such as mustards have been widely known fumigants as they suppress fungal diseases. Despite so many advantages, the issue of competitiveness between cover crop and main crop for resources cannot be ignored and bypassed. Strategic planning, management and manipulation of cover crops system are essential and decisive to reduce competition with the main crop for resources. Though cover crop systems have been in use for centuries, yet environmental concerns raised due to revolutionary inorganic agriculture have paved the way for more exploration and refinement in their use.